Quality Control and Evaluation of Certain Properties of Soaps Available in Butwal Sub-metropolitan City, Nepal - Sharma, Krishna Prasad; Belbase, Anil; Neupane, Umesh (Butwal Campus Journal, 2020)
Abstract available with full text.